MENINGKATKAN PARTISIPASI BELAJAR BIDANG STUDI IPS MATERI KETENAGAKERJAAN MELALUI MODEL DISKUSI THINK PAIR SHARE - Muizzatul Mutsaniah, (Pendidikan Ekonomi, 2013)
This study aims to investigate the application of Think Pair Share learning strategies in improving students participation in the field of social science studies on employment topic. The aim, mainly to determine the activity of the teacher, student participation, student learning outcomes and student responses on the application of Think Pair Share learning strategies. This study was a class action research. The results showed that there was an improvement of student participation from the first cycle to the second cycle of the value of 2.7 to 3.8. The result showed the student learning in a first cycle is 79% increase to 100% in the second cycles, and almost all students enjoyed the Think Pair Share learning strategies.